Character education in learning history of the Diponegoro war material - Afriani, Yesti; Agustiningsih, Nur; Karmela, Siti Heidy (Univeritas Papua, 2022)
This study aims (1) to determine the readiness of teachers to carry out character education in learning the history of the material